P78 Long-term antibiotic prescription in patients relisted for late hepatic artery thrombosis is associated with greater waiting list mortality independent of meld. (6th September 2011) - Smith, M; Leithead, J; Materacki, L; Sagar, V; Gunson, B; Bramhall, S; Mutimer, D; Shah, T
Abstract : Introduction: Optimal prioritisation and medical management of patients with late hepatic artery thrombosis (HAT) awaiting liver transplantation remains unclear. Aim: To examine the association of complications of late HAT and their interventions with liver transplant waiting list mortality. Method: Single centre study of 49 patients listed for late HAT 01/1995–06/2010. Late HAT was defined as occurrence >4 weeks following liver transplantation. Cox regression was adjusted for listing MELD score at all times. Despite increasing waiting time statistical analyses did not demonstrate any influence of listing time period. Results: Mean listing MELD score was 16 (SD 7). 29% of patients demonstrated biliary stricture/s, 20% cholangitis and 63% biloma/abscess/s. The estimated 3- and 12-month transplant-free survival following listing was 85% and 53%, respectively. 36 patients were regrafted, with a median time from listing to transplantation of 45 (IQR 13–167) days. No relationship was demonstrated between the presence of biliary stricture/s (p=0.984), cholangitis (p=0.770) or biloma/abscess/s (p=0.143), and wait-list mortality. Instead, an increasing number of biloma/abscess drain insertions (p=0.038) and long-term (LT) prescription of antibiotics (p=0.029) were linked with an increased risk of death. Multi-drug resistant bacteria (MDRB) were cultured in bile/blood more frequently in those receiving LT antibiotics (44% vs 8%, p=0.004), and MDRB positivity was also a risk factor for waiting list mortality (p=0.033). On multivariate analysis the only predictor of death was LT antibiotics (MELD, HR 1.23; 95% CI 1.04 to 1.44, p=0.013: antibiotics, HR 24.20; 95% CI 1.28 to 455.88, p=0.033). Following regraft, LT antibiotics (p=0.025) and MDRB positivity while listed (p=0.002) remained predictors of patient mortality independent of the preoperative MELD score. The estimated 3- and 12-month post transplant survival of patients with MDRB positivity was 63% and 25%, respectively, and for those without 89% and 86% (log-rank p=0.001). Conclusion: Patients listed for late HAT receiving LT antibiotics are a high risk group who require greater priority for liver transplantation. Our results raise the possibility that by increasing bacterial resistance LT antibiotics may have a detrimental effect on patient survival.